0033 A statewide survey of evidence-based falls prevention programs in massachusetts. (26th April 2015) - Howland, Jonathan; Treadway, Nicole; Taylor, Alyssa; Cicerchia, Carla; Hackman, Holly; Kautz-Mills, Julie
Abstract : Statement of purpose: The Massachusetts (MA) Department of Public Health engaged the Injury Prevention Centre at Boston Medical Centre to develop a state-wide baseline (2012) inventory of evidence-based (EB) community falls prevention programs for MA older adults living independently. Methods/Approach: A survey of organisations serving older adults was deployed in two parts: Part 1 determined if a program had been offered in 2012; the salience of falls prevention for the organisation; and, intention to offer future falls prevention programming. If a falls prevention program had been offered in 2012, the Director designated a Coordinator to provide details. This designation triggered Part 2 which collected Information on the specific programs. For the last program offered, data were collected on number of participants, the training and occupations of program facilitators and program funding. This served as a cross-sectional sample of all programs. Results: Response rates: 55% and 86% for Part 1 and Part 2, respectively. 32% of respondents reported falls prevention programming; 68% indicated intention to offer future programs. Mean falls prevention salience score: 3.68, on a 1–5 scale. 12% offered ≥ 1 EB program. 107 EB programs served 1137 MA older adults. 90.6% were A Matter of Balance and 7.6% were EB Tai Chi. 37% were offered by Area Agencies on Ageing; 46% by Councils on Ageing. 95% of programs had trained facilitators. 42% were facilitated by healthcare professionals. 44% of programs were internally funded. 81% of the programs charged no fees. Conclusions: Infrastructure for deployment of EB falls prevention programs is developing in MA, despite the absence of institutionalised funding, legislative mandates, widespread referrals from healthcare providers, or health insurance reimbursement. Significance and contribution to the field: Methods developed for this study could be adapted by other states wishing to describe community-based falls prevention programming.